IMMUNOLOGY OF INFECTION: MECHANISM OF IMMUNE RESPONSE AND IMPLICATION FOR THERAPEUTIC - Lisa Savitri; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (JURNAL PENA SAINS, 2026)
Infectious diseases, caused by pathogens such as bacteria, viruses, fungi, and parasites, continue to represent a significant global health challenge. The immune system plays a pivotal role in recognizing and eliminating these pathogens, but pathogens have evolved various mechanisms to evade immune responses, resulting in chronic infections and disease progression. This review aims to explore the mechanisms of immune responses to infections, focusing on innate and adaptive immune cells, pathogen recognition, and immune evasion strategies. The review also discusses the therapeutic implications of these findings, highlighting potential targets for developing new treatments. The innate immune response, which includes pattern recognition receptors (PRRs) such as Toll-like receptors (TLRs) and NOD-like receptors (NLRs), serves as the first line of defense. In contrast, the adaptive immune response involves T cells and B cells recognizing specific antigens on pathogens. Despite the immune system's defense mechanisms, pathogens can evade immune detection through antigenic variation and suppression of immune functions. Recent research has provided new insights into immune modulation and therapeutic targets, such as enhancing the innate immune response and targeting specific immune cell subsets. Vaccines remain a critical strategy for preventing infectious diseases. Continued advancements in immunology are crucial for developing more effective interventions to control and treat infectious diseases.